Single Lung Transplant Remains a Viable Option for Patients With Severe Secondary Pulmonary Hypertension. Issue 11 (6th June 2022) - Sunagawa, Gengo; Kehara, Hiromu; Mangukia, Chirantan; Brann, Stacey; Leotta, Eros; Yanagida, Roh; Minakata, Kenji; Shenoy, Kartik V.; Mamary, Albert James; Marchetti, Nathaniel; Cordova, Francis; Criner, Gerard J.; et al.
Abstract : Background: Although double lung transplant is recommended in patients with severe secondary pulmonary hypertension (SPH), our institutional experiences suggest a role for single lung transplant in these patients. Here, we review our experience prioritizing single lung transplant in patients with SPH to minimize their surgical burden. Methods: We conducted a retrospective review of our lung transplant database to identify patients with SPH who underwent single lung transplant. Patients were stratified as either mild SPH (mean pulmonary artery pressure 25–40 mm Hg) or severe SPH (mean pulmonary artery pressure >40 mm Hg). Singe lung recipients without PH transplanted over the same time were also examined. Results: Between January 2017 and December 2019, 318 patients underwent single lung transplantation; 217 had mild SPH (68%), and 59 had severe SPH (18.5%). Forty-two patients without PH underwent single lung transplant. When the groups were compared, significantly higher pulmonary vascular resistance was noted in the severe SPH group, and obesity was noted in both the mild and severe SPH groups. Although the severe SPH group required more intraoperative cardiopulmonary support (37.3% versus 10.3% versus 4.7%, P < 0.05), there were no significant differences in most major postoperative parameters, including the duration of postoperative mechanical ventilation or the incidence of severe primary graft dysfunction. Survival 1 y posttransplant was not significantly different among the groups (93.2% versus 89.4% versus 92.9%, P = 0.58). Conclusions: Our experience supports the option of single lung transplantation with appropriate intraoperative mechanical circulatory support in patients with SPH. This strategy is worth pursuing, especially with ongoing donor lung shortages.